Characteristics of retracted research papers before and during the COVID-19 pandemic - Furuse, Yuki (Frontiers in Medicine, 2024)
Objectives During the COVID-19 pandemic, a large number of research papers were published, and some of them were retracted. The present study aims to reveal the characteristics of retracted papers before and during the pandemic. Methods The study investigated 24,542,394 publications from 1999 to 2022 and analyzed the profiles of retracted papers from the perspectives of year, disease category, country, and journal. Results Retraction rates were generally increasing at least until 2019, and were the highest for “Neoplasms.” The number of publications for “Infections” and “Respiratory Tract Diseases” dramatically rose during the COVID-19 pandemic; however, the retraction rates in the two categories or of COVID-19-related papers were not especially high compared to other diseases. The association for retraction was strongest for China in most disease categories, whereas for COVID-19 papers, other countries showed higher retraction rates than China. In recent years, retracted papers have become less likely to be published in high-impact journals. Conclusions The COVID-19 pandemic does not seem to affect the retractions of research papers much. We should keep monitoring retractions and analyze the effects of pandemics for better science.